ASSESSING THE INFLUENCE OF THE INDUCED TELEWORK ON WOMEN'S EMPLOYMENT IN PORTUGAL - Ekaterina REZNIKOVA; Laura Tereza GOMEZ URQUIJO; Marta ENCISO SANTOCILDES (Challenges of the Knowledge Society)
The COVID-19 pandemic has triggered significant shifts in labor markets worldwide, notably an increase in remote work even as restrictions have eased. This rise in telework has led employers to reconsider its viability and feasibility compared to pre-pandemic norms. However, this sudden transition, coupled with gaps in social policies, has disproportionately impacted existing issues such as gender disparities and labor market inequalities. To explore these dynamics, qualitative interviews were conducted with fifteen Portuguese experts specialising in labor and gender issues, alongside fifteen women who experienced a sudden shift from officebased work to remote work. The study examined how this abrupt change affected women's work processes and contributed to the growing trend of feminization of telework, where more women opt for remote work to balance paid and unpaid responsibilities like household and childcare duties. Data analysis was conducted using MaxQD software. This paper fills a research gap by focusing on female employment, a topic often overlooked in existing literature that predominantly covers general employment trends. The findings shed light on the increasing participation of women in remote work in Portugal, underscoring its negative impact on efforts to create a fairer and more inclusive labor market. Moreover, the study highlights how female telecommuters in Portugal often struggle with blurred boundaries between work and personal life. The findings underscore the need for transformative policies that prioritise positive discrimination in favor of female teleworkers.